2021
DOI: 10.1177/09749306211023621
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Infrastructure, Trade Openness, Foreign Direct Investments and Economic Growth in India

Abstract: This study examines the dynamic interrelationships among infrastructure, trade openness, foreign direct investments (FDI), economic growth, fixed capital formation, labour and inflation rate in the context of India for the period 1970 to 2018 through the application of Toda–Yamamoto (TY) causality test and the auto-regressive distributed lag (ARDL) bounds testing approach to cointegration to offer policy implications of the effectiveness of these important macroeconomic determinants in the short and long-run. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Among variables that could have a positive impact on the ICT infrastructure development is economic growth (Nair et al, 2020;Pradhan, 2019;Pradhan et al, 2021;Sawng et al, 2021;Roger et al, 2022), GDP per capita (Farooqi, 2020), R&D (Lee et al, 2016;Nair et al, 2020), urbanization (Cohen-Blankshtain & Rotem-Mindali, 2016Farooqi, 2020;Pradhan et al, 2021), inward FDI flaws (Arvin & Pradhan, 2014;Samir & Mefteh, 2020), institutional quality (Farooqi, 2020), education and trade openness (Lee et al, 2016). Variables such as economic growth (Maparu & Mazumder, 2021;Pradhan et al, 2021;Sarania, 2021), urbanization (Maparu & Mazumder, 2021;Pradhan et al, 2021), institutional quality (Di Liddo et al, 2019;Cavalieri et al, 2020), trade openness (Sarania, 2021) and inward FDI stock (Samir & Mefteh, 2020) are discussed as ones which can also encourage the development of transport infrastructure.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Among variables that could have a positive impact on the ICT infrastructure development is economic growth (Nair et al, 2020;Pradhan, 2019;Pradhan et al, 2021;Sawng et al, 2021;Roger et al, 2022), GDP per capita (Farooqi, 2020), R&D (Lee et al, 2016;Nair et al, 2020), urbanization (Cohen-Blankshtain & Rotem-Mindali, 2016Farooqi, 2020;Pradhan et al, 2021), inward FDI flaws (Arvin & Pradhan, 2014;Samir & Mefteh, 2020), institutional quality (Farooqi, 2020), education and trade openness (Lee et al, 2016). Variables such as economic growth (Maparu & Mazumder, 2021;Pradhan et al, 2021;Sarania, 2021), urbanization (Maparu & Mazumder, 2021;Pradhan et al, 2021), institutional quality (Di Liddo et al, 2019;Cavalieri et al, 2020), trade openness (Sarania, 2021) and inward FDI stock (Samir & Mefteh, 2020) are discussed as ones which can also encourage the development of transport infrastructure.…”
Section: Methodological Approachmentioning
confidence: 99%
“…This also contributes to regional integration into global and national economic systems, as evidenced by studies such as those by Suarez-Villa and Hasnath (1993), which found that infrastructure construction effectively promotes firms' patent output and encourages industrial innovation (Suarez-Villa and Hasnath 1993). Sarania (2021) found that infrastructure construction can promote economic development by increasing the level of trade openness (Sarania 2021). Netirith and Ji (2022) pointed out that connectivity is important to link the community, regional integration, transportation and the direction of international trade import and export performance (Netirith and Ji 2022).…”
Section: Theoretical Background Of Infrastructure Investment and The ...mentioning
confidence: 99%